2003
DOI: 10.1080/03009740310000409
|View full text |Cite
|
Sign up to set email alerts
|

Hip disability and osteoarthritis outcome scoreAn extension of the Western Ontario and McMaster Universities Osteoarthritis Index

Abstract: To further develop the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC LK 3.0) for people with hip disability with or without hip osteoarthritis (OA), 52 subjects (median age 64 yrs, 35 women) answered a version of the Index with additional dimensions, twice, with a one-week interval. Reproducibility, percentage of zero scores (best possible scores), mean score of symptoms, and importance, were analyzed. This resulted in the Hip disability and osteoarthritis outcome score (HOOS LK 1.1), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
304
1
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(330 citation statements)
references
References 9 publications
5
304
1
8
Order By: Relevance
“…The HOOS is a validated PRO that more precisely captures hip dysfunction in patients with and without underlying osteoarthritis [13,14]. PROs indicated no difference between groups preoperatively (HOOS subscales [ Table 4]: symptoms p = 0.96, pain p = 0.83, activities of daily living 0.769, and quality of life 0.879); SF-12 physical [ Table 5]: p = 0.93; UCLA activity [ Table 5], p = 0.76).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HOOS is a validated PRO that more precisely captures hip dysfunction in patients with and without underlying osteoarthritis [13,14]. PROs indicated no difference between groups preoperatively (HOOS subscales [ Table 4]: symptoms p = 0.96, pain p = 0.83, activities of daily living 0.769, and quality of life 0.879); SF-12 physical [ Table 5]: p = 0.93; UCLA activity [ Table 5], p = 0.76).…”
Section: Methodsmentioning
confidence: 99%
“…The radiographic correction achieved was smaller in patients who had undergone prior pelvic osteotomy surgery than in patients undergoing PAO without prior pelvic surgery. With revision PAOs, the mean correction attained was 19°for LCEA (p \ 0.001, SD 10°; 95% CI, 14-24), 13°for ACEA (p = 0.014, SD 12°; 95% CI, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and À12°for AI (p \ 0.001, SD 9°; 95% CI, À20 to À15) ( Table 3). In comparison, the mean correction attained in the primary cohort was 22°in LCEA (p \ 0.001, SD 10°; 95% CI, 20-26), À17°for AI (p \ 0.001, SD 6°; 95% CI, À16 to À6), and 24°for ACEA (p \ 0.001, SD 12°; 95% CI, [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Methodsmentioning
confidence: 99%
“…Isolated hardware removal was not included in the number of previous surgeries. Baseline clinical scores included modified Harris hip score (mHHS) [9], WOMAC [1,12], and SF-12 [19] scores. Patients were subclassified into five categories based on surgeon-assigned diagnoses (at the time of secondary surgery) and type of previous and secondary surgery including (1) FAI/labral tears; (2) adult hip dysplasia; (3) pediatric hip dysplasia; (4) SCFE; and (5) LCP disease/residual Perthes-like deformities (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The mean Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) 24 increased by 9.6 at final follow-up (p < 0.001), with no complications. Leunig et al 25 reported three cases of mild SCFE (slip angle between 15°a nd 30°) in patients aged between 11 and 15 years treated with arthroscopic osteochondroplasty followed by in situ pinning concomitantly.…”
Section: Figmentioning
confidence: 99%